2012
DOI: 10.1590/s0100-29452012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Radiação gama na conservação de caqui 'Giombo', destanizado e frigoarmazenado

Abstract: RESUMO-o caqui apresenta uma safra curta, sendo necessário estender seu período de comercialização utilizando técnicas adequadas de armazenamento. o objetivo deste trabalho foi avaliar o uso da radiação gama na qualidade pós-colheita de caquis 'Giombo' destanizados. Frutos colhidos meio-maduros e com aproximadamente 50 % da coloração verde, foram destanizados, acondicionados em bandejas de poliestireno expandido (EPS), revestidas por filme plástico de polietileno de baixa densidade (PEBD) e submetidos à radiaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
2
1
2
Order By: Relevance
“…This value is higher than those obtained in "Rama Forte" and "Mikado" persimmon fruits grown in Nova Friburgo (Rio de Janeiro, Brazil) which presented, for the same characteristic, average values of 14.0 and 14.8 °Brix, respectively (Shimizu et al, 2002). Results obtained by Vieites et al (2012) with "Giombo" persimmon fruits grown in Avaré (São Paulo, Brazil) showed lower soluble solids content (19.33 °Brix) as compared to the current study.…”
Section: Yield and Physicochemical Fruit Characteristicscontrasting
confidence: 66%
“…This value is higher than those obtained in "Rama Forte" and "Mikado" persimmon fruits grown in Nova Friburgo (Rio de Janeiro, Brazil) which presented, for the same characteristic, average values of 14.0 and 14.8 °Brix, respectively (Shimizu et al, 2002). Results obtained by Vieites et al (2012) with "Giombo" persimmon fruits grown in Avaré (São Paulo, Brazil) showed lower soluble solids content (19.33 °Brix) as compared to the current study.…”
Section: Yield and Physicochemical Fruit Characteristicscontrasting
confidence: 66%
“…These results are similar to those found in other cultivars, such as Thompson Seedless, which presented approximate values of 0.75 to 0.82 g of tartaric acid 100 mL -1 (Ejsmentewicz et al, 2015;Silva;Silva, 2005). According to Vieites et al (2012), the decrease in acidity is a natural consequence of fruit ripening, in which organic acids are metabolized in the respiratory reaction and converted into non-acidic molecules. We therefore advocate that environmental conditions during the first production cycle may have favored the degradation of organic acids.…”
Section: Quality and Antioxidant Activity Of 'Brs Clara' Grapesmentioning
confidence: 99%
“…The Brazilian production of persimmons has grown in recent years (Brackmann et al, 2013). However, because the harvest is concentrated in just three months of the year and this fruit is very perishable, this hinders their marketing and consumption throughout the year (Vieites et al, 2012). Thus, one way to increase the availability to the consumer and even add more value to the end product is persimmon processing or industrialization, and the development of mixed juices with traditionally accepted, inexpensive fruits, with low perishability that are offered practically all year round, such as oranges and pineapple, are excellent choice.…”
Section: Introductionmentioning
confidence: 99%